Virulência de micro-organismos à Plutella xylostella (L.) (Lepidoptera: Plutellidae) e compatibilidade com inseticidas - Duarte, Rogério Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), is one of the main pest in Brassicaceae family with control based on the indiscriminate use of insecticides, which has provided an increase in the number of cases of resistant populations to different active ingredients. Biological control, by using of entomopathogenic microorganisms is an important tool for the management of this pest. However, the main obstacle in terms of efficiency and conservation of these microbial agents in the field is related to the compatibility with pesticides. The aim of the research was to analyze the susceptibility of P. xylostella to entomopathogenic microorganisms and evaluate the compatibility of the most virulent entomopathogens with insecticides registered for the control of pest complex in cabbage crop. Efficiency of 13 isolates of the entomopathogenic bacterium Bacillus thuringiensis was analyzed, in addition to isolates of the entomopathogenic fungi Beauveria bassiana, Metarhizium rileyi, Isaria fumosorosea, I. sinclairii and Lecanicillium muscarium by performing pathogenicity and virulence tests (LC50 and LT50) on second instar larvae of P. xylostella. The interaction between the isolates and active ingredients was made from the mixture of the insecticide in the culture medium, inoculated with an aliquot of the microorganism suspension after medium solidify, evaluated the number of spores / mL (B. thuringiensis), and the colony growth, the number and conidia viability (entomopathogenic fungi) after seven days the inoculation of these microorganisms. The isolates of B. thuringiensis HD-1, HD-4, HD-11, HD-73 and T-07were the most efficient in P. xylostella control, responsible for overall mortality, with LC50 ranging from 0.75 to 11.66 × 103 spores / mL and TL50 between 25.12 to 34.47 h. The isolates IBCB01, IBCB18, IBCB66 and IBCB87 of B. bassiana, LCMAP101 of M. rileyi and ARSEF7973 of I. sinclairii caused mortality between ...

A traça-das-crucíferas, Plutella xylostella (L.) (Lepidoptera: Plutellidae), é uma das principais pragas da família Brassicaceae, com controle baseado no uso indiscriminado de inseticidas, o que tem propiciado o aumento no número de casos de populações resistentes a diferentes ingredientes ativos. O controle biológico com a utilização de micro-organismos entomopatogênicos constitui uma importante ferramenta para o manejo desta praga. Entretanto, o principal entrave quanto à eficiência e conservação destes agentes microbianos no campo está relacionado à compatibilidade com os agrotóxicos. O objetivo da pesquisa foi analisar a suscetibilidade de P. xylostella a micro-organismos entomopatogênicos e avaliar a compatibilidade dos entomopatógenos mais virulentos com inseticidas registrados para o controle do complexo de pragas da cultura do repolho. Foi analisada a eficiência de 13 isolados da bactéria entomopatogênica Bacillus thuringiensis, além de isolados dos fungos entomopatogênicos Beauveria bassiana, Metarhizium rileyi, Isaria fumosorosea, I. sinclairii e Lecanicillium muscarium, através da realização de testes de patogenicidade e virulência (CL50 e TL50) sobre lagartas de segundo ínstar de P. xylostella. A interação entre os isolados e os ingredientes ativos foi realizada a partir da mistura do inseticida no meio de cultura, sendo inoculada uma alíquota da suspensão do micro-organismo após o meio se solidificar, sendo avaliado o número de esporos/mL (B. thuringiensis) e o crescimento da colônia, o número e a viabilidade dos conídios (fungos entomopatogênicos), após um período de sete dias da inoculação destes micro-organismos. Os isolados HD-1, HD-4, HD-11, HD-73 e T-07 de B. thuringiensis foram os mais eficientes no controle de P. xylostella, responsáveis por ocasionar mortalidade total das lagartas, com CL50 variando entre 0,75 e 11,66 × 103 esporos/mL e TL50 entre 25,12 e 34,47 h. Os isolados...
Keywords: Traça; Pragas agricolas - Controle; Pragas agricolas - Controle biologico; Bacillus thuringiensis; Fungos; Produtos químicos agrícolas; Agricultural pests Biological control